2018
DOI: 10.3389/fpsyg.2018.00068
|View full text |Cite
|
Sign up to set email alerts
|

Returning to Work after Childbirth in Europe: Well-Being, Work-Life Balance, and the Interplay of Supervisor Support

Abstract: Parents returning to work after the arrival of a new son or daughter is an important question for understanding the trajectory of people's lives and professional careers amid current debates about gender equality and work-life balance (WLB). Interestingly, current research concludes that general WLB practices at the workplace may be necessary in the specific case of women returning to work after childbirth because of the particular maternal and infant factors involved. However, WLB practices as a flexible arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…Several models have suggested that dopaminergic neuromodulation enhances exploratory behavior along with the motivation to seek a reward 62, 64, 65. In line with these ideas and related to curiosity, ample evidence in rodents highlights the role of dopamine during exploration and, in turn, its effect on memory consolidation 66, 67, 68.…”
Section: Curiosity Triggers Dopaminergic Neuromodulationmentioning
confidence: 88%
“…Several models have suggested that dopaminergic neuromodulation enhances exploratory behavior along with the motivation to seek a reward 62, 64, 65. In line with these ideas and related to curiosity, ample evidence in rodents highlights the role of dopamine during exploration and, in turn, its effect on memory consolidation 66, 67, 68.…”
Section: Curiosity Triggers Dopaminergic Neuromodulationmentioning
confidence: 88%
“…Workers with a healthy WLB will in turn have better mood, emotions and health, leading to improving attitudes and behaviours towards work and the arrangement of personal affairs. Many studies have focused on investigating the effect of organisational-level WLB and the direct relationship between organisational-level WLB and employee wellbeing [18,53,54]. We focused on the individual-instead of the organisational-level WLB and the moderating effect of subjective wellbeing on the relationship between WLB and employee wellbeing.…”
Section: Multiple Discrepancies Theory Wlb and Subjective Wellbeingmentioning
confidence: 99%
“…Research indicates that these dimensions are highly relevant factors that influence parents' decisions regarding their employment behavior (Abendroth and Dulk 2011;Kossek et al 2010). Studies have revealed the positive effects of supervisor support on work−life balance (Abendroth and Dulk 2011;Hilbrecht et al 2008;Kossek et al 2010;Lucia-Casademunt et al 2018) but also on the working hours of mothers (Abendroth et al 2012). Although findings with regard to support from colleagues are still scarce (Kossek et al 2010), it appears to be negatively related to work−family conflict (Thompson and Prottas 2005).…”
Section: Supportiveness Of the Work Environmentmentioning
confidence: 99%